Inelastic Buyers and Competition. (13th December 2017) - Calzolari, Giacomo; Ichino, Andrea; Manaresi, Francesco; Nellas, Viki
Abstract: We measure precisely how competition limits the capacity of sellers to appropriate surplus from less elastic consumers. The evidence originates from pricing strategies of Italian pharmacists in response to exogenous inflows of parents of newborn babies among their buyers. Population‐based laws allow us to use a regression discontinuity design to compare different competitive environments. While more newborn babies have no effect on the price of hygiene products under intense competition, we observe a price increase when competition is low. This effect is not driven by increasing costs because for nappies, demanded by newborns only, we see no effect independently of competition.